2019
DOI: 10.1021/acs.orglett.9b01013
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Synthesis of N-Terminal Cysteinyl Thioesters via β,γ-C,S Thiol-Michael Addition

Abstract: Dehydroalanine (ΔAla) is a highly electrophilic residue that can react efficiently with sulfur nucleophiles to furnish cysteinyl analogues. Herein, we report an efficient synthesis of N-terminal cysteinyl thioesters, suitable for S,Nacyl transfer, based on β,γ-C,S thiol-Michael addition. Both ionic and radical-based methodologies were found to be efficient for this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
8
0
2
Order By: Relevance
“…Recently, the Scanlan group applied radical TEC coupling to dehydroalanine (Dha) for synthesis of N-terminal cysteinyl thioesters suitable for S, N-acyl transfer (Petracca et al, 2019). Radical TEC between N-protected Dha and either thioacetic acid or a glycine thioacid was effected using DPAP and MAP in aqueous buffer at pH 6.…”
Section: Other Functionalizations and Applicationsmentioning
confidence: 99%
“…Recently, the Scanlan group applied radical TEC coupling to dehydroalanine (Dha) for synthesis of N-terminal cysteinyl thioesters suitable for S, N-acyl transfer (Petracca et al, 2019). Radical TEC between N-protected Dha and either thioacetic acid or a glycine thioacid was effected using DPAP and MAP in aqueous buffer at pH 6.…”
Section: Other Functionalizations and Applicationsmentioning
confidence: 99%
“…A publication [117] by Mallick et al reported comparable results, employing the same reactions conditions previously developed in the Sahoo group (Section 2.4, Dutta et al). Mallick and co-worker's approach employed a N-hydroxyphthalimide-mediated radical cyclization of yne-dienones, yielding 3-thioaryl- [6,6]-dihydrochromenone derivatives. Altering the substituents of the aryl thiol, or the functional groups presented by the yne-dienone were again well tolerated in the cascade.…”
Section: State Of the Artmentioning
confidence: 99%
“…Since the turn of the millennium, organosulfur compounds have garnered substantial interest in the fields of medicinal chemistry, chemical biology and material science [1][2][3][4][5][6][7]. Of the diverse biochemical processes involving free radicals, many are thiyl radical mediated, highlighting the chemoselectivity, efficiency and biocompatibility of these reactive intermediates [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations